2006
DOI: 10.1128/aem.00255-06
|View full text |Cite
|
Sign up to set email alerts
|

Applications of a Rapid Endospore Viability Assay for Monitoring UV Inactivation and Characterizing Arctic Ice Cores

Abstract: We have developed a rapid endospore viability assay (EVA) in which endospore germination serves as an indicator for viability and applied it to (i) monitor UV inactivation of endospores as a function of dose and (ii) determine the proportion of viable endospores in arctic ice cores (Greenland Ice Sheet Project 2 [GISP2] cores; 94 m). EVA is based on the detection of dipicolinic acid (DPA), which is released from endospores during germination. DPA concentrations were determined using the terbium ion (Tb 3؉ )-DP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 49 publications
2
37
0
Order By: Relevance
“…We note that enzymatic activity has been detected in actinomycete spores at 40°C (45), which may indicate some capability for damage repair. However, Shafaat and Ponce (46) have shown that spores are only Ϸ1% as abundant as vegetative cells in GISP2 ice; at subzero temperature, the total rate of damage repair of spores is thus negligible relative to the rates shown by the purple lines in Fig. 3.…”
Section: Discussionmentioning
confidence: 99%
“…We note that enzymatic activity has been detected in actinomycete spores at 40°C (45), which may indicate some capability for damage repair. However, Shafaat and Ponce (46) have shown that spores are only Ϸ1% as abundant as vegetative cells in GISP2 ice; at subzero temperature, the total rate of damage repair of spores is thus negligible relative to the rates shown by the purple lines in Fig. 3.…”
Section: Discussionmentioning
confidence: 99%
“…This communication shows that low concentrations of Tb 3ϩ and some other multivalent metal ions strongly inhibit the germination of coat-deficient spores. This finding is notable, as these same low Tb 3ϩ concentrations are used to assay viable spores by measuring DPA release in spore germination (26,28,29,31,32). Since coat-deficient spores have viability comparable to that of intact spores (8,15), Tb 3ϩ -based assays of spore viability could yield false-negative results with coat-deficient spores.…”
mentioning
confidence: 93%
“…DPA forms a strong 1:1 highly fluorescent complex with terbium (Tb 3ϩ ) ions, and spore quantification by Tb 3ϩ -DPA fluorescence takes only a few minutes (4,12). DPA is also released in the first minutes of spore germination (23), and since germination is essential for spore viability, Tb 3ϩ -DPA fluorescence has been used to detect spore germination, and there is a good correlation between DPA release and spore viability (4,26,28,29,31,32). However, we report a flaw in the latter assay of spore viability, as Tb 3ϩ and some other multivalent metal cations strongly inhibit germination of coat-deficient spores.…”
mentioning
confidence: 99%
“…Previously, we reported a related method where germinating endospores were enumerated in bulk suspension by luminescence spectroscopy (i.e., spectro-EVA), where Tb-DPA luminescence intensities were tabulated against a B. atrophaeus endospore calibration curve (28). Results obtained by a comparison of EVA to spectroEVA showed that the two methods are in good agreement (see Fig.…”
Section: Resultsmentioning
confidence: 53%